Does the Preoperative Prognostic Nutritional Index Predict Survival in Patients with Liver Metastases from Colorectal Cancer Who Underwent Curative Resection? - Zhao, Yujie (J Cancer, 2018)
Purpose: The prognostic nutritional index (PNI) has been correlated with long-term outcomes in various cancer patients. However, the relationship between the PNI and long-term outcomes in patients with colorectal cancer liver metastasis (CRLM) who have undergone liver surgery have not been fully investigated. In this study, we aimed to identify the impact of the preoperative PNI on the long-term oncologic outcomes of patients with CRLM who have undergone curative hepatic resection. Methods: A total of 243 CRLM patients who underwent curative hepatic resection for liver metastases in the Sun Yat-sen University Cancer Center between September 1999 and July 2015 were enrolled, and their medical records were analyzed retrospectively. The preoperative PNI was calculated as 10× the serum albumin concentration (g/dL) + 0.005 × the total lymphocyte count (per mm(3)). The PNI was compared according to the statuses of clinicopathological features. In addition, the regression-free survival (RFS) and overall survival (OS) were analyzed according to the preoperative PNI using univariate and multivariate analyses. Results: The optimal cut-off value of the preoperative PNI was set at 48.5 using the X-tile software. Older patients and those who had undergone synchronous hepatic resection were more likely to belong to the low PNI group (≤48.5) (all P < 0.05). In multivariate analyses, PNI > 48.5 was associated with markedly better survival outcomes as an independent factor, both for OS and RFS. Conclusion: For patients with CRLM undergoing curative hepatic resection, preoperative PNI is a simple and efficient indicator (cut-off value=48.5) for preoperative estimation of oncologic outcomes.